Endovascular Treatment of Experimental Wide Neck Aneurysms: Comparison of Results Using Coils or Cyanoacrylate with the Assistance of an Aneurysm Neck Bridge Device - Raymond, Jean; Salazkin, Igor; Georganos, Stavros; Guilbert, Francois; Desfaits, Anne-Cecile; Gevry, Guylaine; Weill, Alain; Roy, Daniel (American journal of neuroradiology : AJNR, 2002)
Endovascular treatment of wide neck aneurysms often results in incomplete occlusion or aneurysm recurrence. The two goals of the present study were to compare results of coil embolization with or without the assistance of an aneurysm neck bridge device (ANBD) and to explore the use of this instrument to control cyanoacrylate embolization. Wide necked bifurcation aneurysms were constructed in 28 dogs. Coil embolization of the aneurysms was performed 2 to 4 weeks later, with (n = 11) or without (n = 10) ANBD assistance. In seven other animals, embolization was performed with cyanoacrylate, injected under the protection of ANBDs. Angiographic results were compared immediately after and at 3 and 12 weeks. Neointima formation at the neck was also compared between groups at 12 weeks. Initial angiographic results and recurrences at 12 weeks were not significantly different in aneurysms coiled with or without ANBDs. Neointimal scores were also similar. The use of one ANBD at the neck was not sufficient to safely deliver cyanoacrylate into aneurysms. Cyanoacrylate embolization led to improved angiographic results (P =.05) and to better neointimal sealing of the neck of the aneurysms at 12 weeks (P =.004). ANBDs did not prevent recanalization and recurrences after coil embolization of wide neck aneurysms in this animal study. ANBD-assisted cyanoacrylate embolization was unsafe but could decrease recurrences at 12 weeks.